2015
DOI: 10.1530/erc-15-0081
|View full text |Cite
|
Sign up to set email alerts
|

The 8q24 rs6983267G variant is associated with increased thyroid cancer risk

Abstract: The G allele of the rs6983267 single nucleotide polymorphism, located on chromosome 8q24, has been associated with increased risk of several cancer types. The association between rs6983267G and thyroid cancer has been tested in different populations, mostly of European ancestry, and has led to inconclusive results. While significant associations have been reported in the British and Polish populations, no association has been detected in populations from Spain, Italy and the USA. To further investigate the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…One study [ 52 ] was treated as 9 independent case groups because nine cancer types were studied. Moreover, we retrieved 25 separated investigations from 9 articles [ 8 , 10 , 39 , 42 , 54 , 61 , 74 , 83 , 88 ]. Finally, a total of 78 separate studies involving 73,996 cases and 96,741 controls were included in our meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…One study [ 52 ] was treated as 9 independent case groups because nine cancer types were studied. Moreover, we retrieved 25 separated investigations from 9 articles [ 8 , 10 , 39 , 42 , 54 , 61 , 74 , 83 , 88 ]. Finally, a total of 78 separate studies involving 73,996 cases and 96,741 controls were included in our meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a germline variant of HABP2 was shown to be associated with papillary thyroid carcinoma in an extended kindred, 20 although the validity of this finding has been questioned. 21,22 …”
Section: Differentiated Thyroid Carcinomamentioning
confidence: 99%
“… [9] Recent genome-wide association (GWA) and candidate studies in Europeans have identified TC risk alleles on chromosomes 2q35 (rs966423), 8p12 (rs2439302), 8q24 (rs6983267), 9q22 (rs965513), and 14q13 (rs944289 and rs116909374). [ 10 11 12 13 ] The effects of some of these known TC variants have been tested in independent populations and so far, most of these variants have been replicated in populations of British, [14] Japanese, [15] and Chinese[ 16 17 ] ancestry. However, to our knowledge, these known single nucleotide polymorphisms (SNPs) have not been comprehensively tested in any South American population.…”
Section: Introductionmentioning
confidence: 99%